Peer-to-peer energy trading in distribution systems - Lim, Yi Kai (2019)
With Singapore rapidly transiting into a decentralized power system, there is a need for a new power market model to manage the energy balance within distribution systems (locally). This report proposes a Peer-to-Peer (P2P) market model incorporating demand response to trade in a distribution network. The P2P auction algorithm maximizes the economic surplus (ES) for retailers that own distributed energy resources (DERs). A demand response model is then incorporated to further increase the ES of retailers, through a load shifting algorithm. The P2P market allows DERs to trade energy within a local distribution network. While demand response helps to facilitate the balance of supply and demand within a distribution network. A retailer will be equipped with a Battery Energy Storage System (BESS) and a photovoltaic (PV) panel for storing and producing energy respectively. Depending on the amount of energy produced by the PV panel and the amount of energy currently stored in the BESS, the retailer can then decide to award bidders in a given time slot. An energy trading mechanism in a two-microgrid community is also proposed. This mechanism allows two different microgrids to support one another when either side has low supply. Through case studies of each proposed mechanism, it is shown to increase the ES of retailers.